2020
DOI: 10.1186/s12872-020-01625-8
|View full text |Cite
|
Sign up to set email alerts
|

Distal transradial access: a review of the feasibility and safety in cardiovascular angiography and intervention

Abstract: Background: Transradial access (TRA) has been considered as the default choice in cardiac catheterization. Although infrequent, vascular complications of this approach remain. Recently, the distal transradial approach (dTRA) in cardiac catheterization was reported by interventionalists. Methods: We retrieved the relevant literatures and reviewed the safety and feasibility of this novel approach in cardiac catheterization. Results: The dTRA for cardiac intervention has superior safety and satisfaction. As a nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
51
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 63 publications
2
51
0
3
Order By: Relevance
“…The puncture of the distal radial artery has some caveats because of anatomical features such as the superficial position of the artery and the bone basement. The puncture site in the DRA is either the distal radial artery of the anatomic snuffbox or the more distal radial artery, which is located on the vertex of the angle between the tendon of the extensor pollicis longus and the second metacarpal bone[ 7 ]. Some studies showed that the diameter of distal radial artery was smaller and might have the increased tortuosity and angulations in comparison to forearm radial artery[ 25 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The puncture of the distal radial artery has some caveats because of anatomical features such as the superficial position of the artery and the bone basement. The puncture site in the DRA is either the distal radial artery of the anatomic snuffbox or the more distal radial artery, which is located on the vertex of the angle between the tendon of the extensor pollicis longus and the second metacarpal bone[ 7 ]. Some studies showed that the diameter of distal radial artery was smaller and might have the increased tortuosity and angulations in comparison to forearm radial artery[ 25 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The antegrade flow through the superficial palmar arch can be maintained during compression of the distal radial artery, resulting in a low risk of retrograde thrombus formation[ 6 ]. The second possibility was the shorter duration of hemostasis with the DRA[ 7 ], which appeared to be related to the structure of the anatomic snuffbox with a bony basement surrounded by tendons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While a "radial first" approach has led to decreased access site complications, its association with radial-specific complications such as radial artery occlusion (RAO), pseudoaneurysm, and arterial spasm led to further refine-ment of this access strategy [6,7]. A distal trans-radial approach is increasingly recognized as a feasible alternative arterial access [6][7][8][9].…”
mentioning
confidence: 99%
“…While a "radial first" approach has led to decreased access site complications, its association with radial-specific complications such as radial artery occlusion (RAO), pseudoaneurysm, and arterial spasm led to further refine-ment of this access strategy [6,7]. A distal trans-radial approach is increasingly recognized as a feasible alternative arterial access [6][7][8][9]. The use of retrograde recanalization of an occluded radial artery through the distal radial artery (dRA) for perioperative monitoring was first described in 2011; however, its use in cardiac catherization was only introduced in 2017 [8,9].…”
mentioning
confidence: 99%